2020
DOI: 10.1080/23802359.2020.1735277
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the Hydrophis melanocephalus slender-necked sea snake (Squamata, Elapidae)

Abstract: We here report the complete mitochondrial genome of the Hydrophis melanocephalus slender-necked sea snake from Okinawa, Japan. Its length is 17,182 bp, consisting of 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and three non-coding regions, providing the basis for further phylogenetic and evolutionary studies of sea snakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…MK775531; 18,259 bp) [ 42 ] and H. melanocephalus (Accession No. MK775532; 17,182 bp) [ 43 ] overlapped with the species sequenced in this study. However, mtDNA sequences reported in these studies for E. ijimae and H. melanocephalus were much shorter than those determined in this study ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MK775531; 18,259 bp) [ 42 ] and H. melanocephalus (Accession No. MK775532; 17,182 bp) [ 43 ] overlapped with the species sequenced in this study. However, mtDNA sequences reported in these studies for E. ijimae and H. melanocephalus were much shorter than those determined in this study ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the course of the present study, complete mtDNA sequences were reported for three semiaquatic sea snakes of the genus Laticauda and several fully aquatic sea snakes of the genera Emydocephalus and Hydrophis (all in the subfamily Hydrophiinae) [ 40 , 41 , 42 , 43 , 44 , 45 ]. Among them, E. ijimae (Accession No.…”
Section: Discussionmentioning
confidence: 99%